Secure Digital Camera Based Fingerprint Recognition System - Hiew, Bee Yan (2008)
Touch-less fingerprint recognition has been receiving attention recently and it imposes a competency for a further advancing of this technology as it frees from the problems in term of hygienic, maintenance and latent fingerprints.